1992
DOI: 10.1210/endo.131.3.1505485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypothyroidism on Sertoli cell proliferation and differentiation and hormone levels during testicular development in the rat.

Abstract: In this study we show that 6-propyl-2-thiouracil (PTU) treatment of Wistar rats from birth up to day 26 p.p. retards the morphological differentiation of Sertoli cells, and prolongs the proliferation of these cells up to day 30. Sertoli cell numbers per testis, determined at day 36, were increased by 84% compared to controls. PTU treatment increased serum thyroid-stimulating hormone (TSH) levels and reduced serum levels of thyroxine (T4) from 5 days onwards, indicative of severe hypothyroidism. Follicle-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
87
1
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 7 publications
13
87
1
2
Order By: Relevance
“…Therefore, neonatal hypothyroidism for about 3 weeks may affect FSH secretion from the pituitary gland throughout life, and an especially significant reduction of FSH levels was apparent after 7 weeks of age in rdw rats. This corresponds well with the finding of a previous report in which hypothyroidism was induced in rats approaching puberty [19,28] and suggests that thyroid hormone deficiency may seriously affect FSH secretion in male rats [30,31]. The depressed serum level of FSH may be the cause of delayed maturation of Sertoli cells in hypothyroid rats [28,32,33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, neonatal hypothyroidism for about 3 weeks may affect FSH secretion from the pituitary gland throughout life, and an especially significant reduction of FSH levels was apparent after 7 weeks of age in rdw rats. This corresponds well with the finding of a previous report in which hypothyroidism was induced in rats approaching puberty [19,28] and suggests that thyroid hormone deficiency may seriously affect FSH secretion in male rats [30,31]. The depressed serum level of FSH may be the cause of delayed maturation of Sertoli cells in hypothyroid rats [28,32,33].…”
Section: Discussionsupporting
confidence: 92%
“…The FSH levels of rdw rats were markedly lower than those of N rats at 7 w and later. Earlier reports showed that FSH levels reduce during the immature stages in chemically induced hypothyroid rats [19,28,29], and that FSH l e v e l s i n t r a n s i e n t h y p o t h y r o i d r a t s a r e permanently reduced through even much later euthyroid periods of life [19]. The duration of the hypothyroid state resulting from transient hypothyroidism induced by PTU was almost the same as that caused by congenital hypothyroidism in rdw rats, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Several other factors have been demonstrated to regulate Sertoli cell development in the time interval under investigation here, including thyroid hormone (Cooke & Meisami 1991, Van Haaster et al 1992, activin (Boitani et al 1995, Fragale et al 2001, Buzzard et al 2003, glial cell line-derived neurotrophic factor (GDNF) (Hu et al 1999), interleukin-1 (Petersen et al 2002), and transforming growth factor (TGF) and epidermal growth factor (Petersen et al 2001). Interactions between these factors and FSH-mediated regulation of Sertoli cell function is not well understood, though two previously identified FSH regulated target genes, cyclin D2 (Buemer et al 2000) and DMRT-1 (Raymond et al 2000) are potential mediators.…”
Section: Sertoli Cell Developmentmentioning
confidence: 99%
“…Transient neonatal hypothyroidism in rats produces unprecedented increases of 80 and 140% in adult testis weight and sperm production respectively . This increase in testis size results primarily from increased Sertoli cell proliferation during neonatal and juvenile life (van Haaster et al 1992) and consequent larger populations of adult Sertoli and germ cells (van Haaster et al 1992, Hess et al 1993. Sertoli cells express thyroid hormone receptor (TR) and its mRNA during the neonatal period ( Jannini et al 1990) and 3,3 ,5-triiodothyronine (T 3 ), the biologically active thyroid hormone, directly inhibits Sertoli cell proliferation in vitro .…”
Section: Introductionmentioning
confidence: 99%